Combining ability evaluation in orange flint lines of maize - Nestares, Graciela; Frutos, Edith; Eyhérabide, Guillermo (Pesquisa Agropecuária Brasileira, 1999)
In species that show heterosis, information about combining ability with genetically divergent testers is useful to classify the germplasm in heterotic groups. The objective of this study was to evaluate 48 orange flint maize (Zea mays) lines for their combining ability with the testers: sB73 and sMo17 from the Reid x Lancaster pattern and with the flint testers HP3 and P5L2 from the local orange flint pattern during the 1991/92 season at four environments. Analyses of variance were computed for each environment separately and combined across environments for: seed yield, ear height, days to 50% silk, number of ear rows, ear length and diameter, 300 kernels weight, and test weight. Spearman correlation coefficients for grain yield of testcrosses with each tester were computed. Line x tester interactions were highly significant for the majority of the traits and there was no correlation between the merit order of lines based on testcrosses performance. These results suggest the importance of non-additive effects and the ability of the testers to rank the lines.
Keywords: Zea mays; testers; testcrosses